2010
DOI: 10.1007/s00417-010-1575-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of polypoidal choroidal vasculopathy in Chinese patients

Abstract: The majority of Chinese PCV patients were male, unilateral, and showed macular polyps. Drusen, serous PED, hemorrhagic PED, and neuroretinal detachment on OCT were commonly seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…The incidence of choroidal vascular hyperpermeability in our patients was comparable to the previously reported values in It has been reported previously that PCV can even develop in patients between 20 and 40 years old [7,8]. In the present study, the youngest patient diagnosed with PCV was 43 years old.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The incidence of choroidal vascular hyperpermeability in our patients was comparable to the previously reported values in It has been reported previously that PCV can even develop in patients between 20 and 40 years old [7,8]. In the present study, the youngest patient diagnosed with PCV was 43 years old.…”
Section: Discussionsupporting
confidence: 93%
“…In clinical practice, we sometimes encounter PCV patients aged <50 years; and such patients have already been included in previous PCV studies from various groups [1,[6][7][8]. However, the characteristics and treatment outcome in this particular sub-group of patients have not been separately analyzed.…”
Section: Introductionmentioning
confidence: 98%
“…A study examining a Caucasian population found that ABCA1 was significantly associated with the progression of drusen and suggested that variants in the ABCA1 gene were involved in drusen initiation and accumulation which had a part in the progression of AMD [20]. Drusen are not an unusual feature of PCV in Asian populations [36,37]. However, there was no evidence of drusen revealing a significant difference in the final status of the retina or in the final visual acuity of patients with PCV [36].…”
Section: Discussionmentioning
confidence: 99%
“…PCV lesions tend to bleed easily, with a rate of 30-63.6% for subretinal haemorrhage 6-8 and 4.5-19.9% for vitreous haemorrhage (VH). 7,8 In the clinical course of PCV, haemorrhage is usually acute, and visual acuity declines abruptly. Visual prognosis may be limited, with prolonged dense haemorrhages under the RPE or recurrent haemorrhages that lead to RPE and outer retina degeneration.…”
Section: Introductionmentioning
confidence: 99%